Papel dos receptores adrenérgicos alfa2/imidazólicos do núcleo parabraquial lateral no controle hidrossalino durante a desidratação extracelular - Cabral, Kriss Alvarenga (2012)
Alpha2 adrenergic receptor activation with bilateral injections of moxonidine into the lateral parabrachial nucleus (LPBN) strongly increases 0.3 M NaCl intake by rats treated with the diuretic furosemide (FURO, 10 mg/kg b.w.) combined with low dose of the angiotensin converting enzyme inhibitor captopril (CAP, 5 mg/kg b.w.) injected subcutaneously (sc). Previous studies have shown that the LPBN participates in the modulation of renal and hormonal responses during increased plasma osmolarity and isotonic volume expansion. However, the effects of LPBN moxonidine injection on urinary volume and sodium excretion, hormonal responses and cardiovascular changes were not yet evaluated in fluid depleted rats, with or without free access to fluids. Male Wistar rats (290-310 g) with bilateral stainless steel guide-cannulas implanted into the LPBN were treated with sc FURO + CAP 45 min before bilateral injections of vehicle or moxonidine (0.5 nmol/0.2 ìl) into the LPBN. Urine collection started 15 min after LPBN injections and sodium excretion and urinary volume were evaluated for 2 hours, with or without free access to water and sodium during this period. Another group of FURO + CAP-treated rats received intragastric loads of NaCl solutions at concentrations similar to the mix of water and 0.3 M NaCl ingested by rats treated with FURO + CAP and moxonidine into the LPBN (6 ml of 0.17 M NaCl each load at 20 and 35 min and 9 ml of 0.13 M NaCl at 45 min after LPBN injections), instead of free access to water and sodium during urine collection. Bilateral injections of moxonidine into the LPBN did not change sodium excretion (488 ± 135, vs. vehicle: 376 ± 75 ìEq/1 h) or urinary volume (2.5 ± 0.7, vs. vehicle: 2.5 ± 0.3 ml/1 h) in fluid depleted rats without access to fluids. When rats had available water and sodium, moxonidine into the LPBN increased sodium (18.83 ± 2.69, vs. vehicle 1.68 ± 0,79 ml/2 h) and water intake (17.47 ± 1.33 vs. vehicle 8.63 ± 1.68 ml/2 h) and also sodium excretion (1277.3 ± 237.85 vs. vehicle 462.88 ± 84.27 ìEq/2 h) and urinary volume (7.38 ± 1.06 vs. vehicle 3.13 ± 0.56 ml/2 h). This increase in ingestion was not counterbalanced by the excretion, thus resulting in a positive sodium and water balance. However, moxonidine injected into the LPBN decreased sodium excretion (462 ± 127, vs. vehicle: 888 ± 122 ìEq/1 h) and urinary volume (2.5 ± 0.5, vs. vehicle: 4.5 ± 0.5 ml/1 h) in fluid depleted rats that received fluid loads. In order to evaluate if moxonidine into the LPBN could change arginine vasopressin (AVP) and oxytocin (OT) plasma levels, male Wistar rats were treated with sc FURO + CAP 45 min before bilateral injections of vehicle or moxonidine (0.5 nmol/0.2 ìl) into the LPBN. Fifteen minutes later, some rats had 30 min-period free access to water and 0.3M NaCl while others were maintained without access to fluids during the same period. Blood samples were collected 45 min after LPBN treatment. The results show that plasma levels of AVP are increased in FURO+CAP- treated rats with moxonidine into LPBN and no access to fluids, but not when the rats had access to fluids. There are no changes in OT plasma levels among the different treatments. Analysis of the cardiovascular parameters in similar protocols shows that moxonidine did not change mean arterial pressure (MAP) in rats without access to fluids, while in rats with free access to water and sodium, moxonidine increased MAP when compared to basal levels. This result suggests that the increase in water and sodium intake is not due to important changes in MAP in rats treated with moxonidine, but that the increased ingestive behavior may affect MAP. Therefore, present results suggest that moxonidine injected into the LPBN in fluid depleted rats produces strong 0.3 M NaCl and water intake and decreases renal sodium excretion and urinary volume, suggesting that moxonidine into this area activates mechanisms that facilitate sodium/water retention and body fluid volume expansion during extracellular dehydration.